A palimpsest of practice-led inquiry: A conversation - Hill, Geof William; Duffy, Ana (Journal of Academic Writing, 2023)
This paper aims to interrogate a writer-researcher’s journey through practice-led inquiry (Gray, 1996) within a broader discourse that acknowledges academic writing as contested. Indeed, the quest of a migrant writer for recognition of their writing in another land requires a deep understanding of the many layers that make up the provenance of their writing practice: A second language, and both their cultural identity and literary background, provide layers of knowledge and experience that fuse to form a ’style’ and ultimately a writing ‘niche’. The readership of their writing carries its own provenance and therefore the additional bias of ‘the home ground’. As it reads in the title, palimpsest, in its figurative sense, is a notion that implies levels of meaning in a literary work. Although not the first writer to use the concept figuratively, it was Thomas De Quincey who wrote an essay entitled “The Palimpsests” (1845), which would inaugurate “the substantive concept of the palimpsest” (Dillon, 2005, p. 243). Similarly, Barthes (1989, p. 99) referred to a text as a layered discourse, an onion, a superimposed construction of skins (of layers, of levels, of systems) whose volume contains, finally, no heart, no core, no secret, no irreducible principle, nothing but the very infinity of its envelopes—which envelop nothing other than the totality of its surfaces. As a writer surfaces, discriminates, and understands the different layers that fashion their writing, and wields their particular use of English as a second language, their practice becomes more authentic. That authenticity becomes a dual threshold element of an exegesis argument, representing faithfulness to the practitioner, and translating or bridging the gap between first language readers and second language voices.